Portrait of Indonesian and Pakistan EFL Students’ Engagement in Online Classroom Based on Neuroscience Approach - Rukminingsih, Rukminingsih; Novianti, Hartia; Anees, Muhammad; Rukmi, Nala Sita (Journal of Languages and Language Teaching, 2024)
The integration of neuroscience principles in online teaching can enhance student engagement and create a more engaging and brain-friendly learning experience. This study aims to portray the comparation of Indonesian and Pakistan EFL students’ behaviour,  cognitive and emotional  engagement in online classroom based on neuroscience  approach.  The participants in this research were students from Indonesian and Pakistan EFL students.  The purposive sampling was used to select the participants who were taking from students of STKIP PGRI Jombang of English language education students from Indonesia and students of Government College Peshawar, Pakistan. This study employed a mixed case study by using a quantitative and qualitative data. The instruments of this study were close- ended and open-ended questionnaires. close-ended questionnaire. The quantitative data was analyzed by using descriptive statistics   and the qualitative data was analyzed by thematic analysis. The findings showed that online learning in Indonesia and Pakistan shown to have positive levels of   behavioral, cognitive and emotional engagement. The most positive engagement from both Indonesia and Pakistan students was behavioral engagement. Then, students’ cognitive engagement was more positive than emotional engagement.  Then the finding also showed that the students engagement in Pakistan students was high positive level than Indonesia students.